Paracetamol-Induced Stevens Johnson Syndrome and Cholestatic Hepatitis - Slim, Raoudha; Fathallah, Neila; Aounallah, Amina; Ksiaa, Mehdi; Sriha, Badreddine; Nouira, Rafiaa; Ben Salem, Chaker (Current Drug Safety, 2015)
Stevens-Johnson syndrome (SJS) is an uncommon life-threatening skin disease, generally induced by drugs. Extracutaneous manifestations of the syndrome can occur, and may involve the conjunctiva, buccal mucosa, gastrointestinal and genitourinary tracts. Cholestatic hepatitis has been rarely described in SJS. A 29-year-old woman was admitted with generalized cutaneous eruption. A self-medication with paracetamol had been started three days earlier. Clinical signs and skin biopsy were consistent with SJS. Five days later, the patient developed jaundice. Serial liver function tests showed rising transaminases, bilirubin, alkaline phosphatase and γ-glutamyl transferase. Liver biopsy was performed and was consistent with the diagnosis of drug-induced cholestatic hepatitis. Adequate supportive care was provided to the patient. Skin lesions disappeared within two weeks. Jaundice disappeared progressively, and liver tests returned to normal. Herein, we report the first case of SJS associated with cholestatic hepatitis after ingestion of therapeutic doses of paracetamol.
Keywords: hepatitis